2019
DOI: 10.1590/1984-0462/;2019;37;3;00011
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Morbidity Near Miss in Tertiary Hospitals in a Capital of Northeast Brazil

Abstract: Objective: To characterize near miss neonatal morbidity in tertiary hospitals in a capital city of Northeast Brazil based on Health Information Systems, and to identify differences regarding indicators of near miss cases, allowing the surveillance of newborns with risk of death.Methods: A cross-sectional study carried out in hospitals with neonatal intensive care unit, whose neonatal near miss cases in 2012 were identified from a deterministic linkage between the Mortality Information System and the Live Birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
2
9
0
6
Order By: Relevance
“…The result of this study is in line with similar other study conducted in Northeastern Brazil [12] and Uganda [16]. However, the nding of this study was inconsistent with similar studies conducted worldwide: low and middle income countries in Africa [20] and three similar studies in Brazil [3,5,14]. The observed high prevalence in this study might be due to the referral nature of the health institutions where an increased probability of attending more complicated cases from the catchment area and neighboring region.…”
Section: Discussionsupporting
confidence: 61%
“…The result of this study is in line with similar other study conducted in Northeastern Brazil [12] and Uganda [16]. However, the nding of this study was inconsistent with similar studies conducted worldwide: low and middle income countries in Africa [20] and three similar studies in Brazil [3,5,14]. The observed high prevalence in this study might be due to the referral nature of the health institutions where an increased probability of attending more complicated cases from the catchment area and neighboring region.…”
Section: Discussionsupporting
confidence: 61%
“…It is estimated that the number of survivors from a NNM event is three-to six-times higher than the number of neonatal deaths. 3,11,12 Even though the causes of neonatal morbidity and mortality are preventable and treatable, and the fact that lowcost and effective interventions exist, there has been no significant decline in neonatal morbidity and mortality. 13 According to the Ethiopia Demographic and Health Survey (commonly referred to as the EDHS) 2016, neonatal mortality declined from 49 deaths per 1,000 live births in 2000 to 29-36 deaths per 1,000 births in 2016, a reduction of 41% over the past 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…According to the classification criteria applied ( 13 ), 2.2 cases of near miss were identified for each neonatal death, which was higher than the findings in earlier Brazilian studies that addressed the feasibility of the NNM concept ( 13 , 14 ). The scarcity of research of NNM in twins makes it difficult to compare these rates and rates within this specific population, yet our findings suggest that twins have worse outcomes for severe neonatal morbidity.…”
Section: Discussionmentioning
confidence: 64%
“…Variables, such as low maternal education level, race/skin color of mixed mothers, women without partners, and lower socioeconomic classes are widely debated since they show an association with increased neonatal morbidity and mortality ( 14 , 18 ). Although twin pregnancies are associated with Brazilian regions with the highest human development index, higher education level, and high maternal age (>35 years), this study showed no relationship between NNM and maternal socioeconomic and demographic conditions ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation